Nickel-Catalyzed Denitrated Coupling Reaction of Nitroalkenes with Aliphatic and Aromatic Alkenes - Zhang, Na; Quan, Zheng-Jun; Wang, Xi-Cun (Advanced synthesis & catalysis, 2016)
A simple and practical denitrated coupling reaction of nitroalkenes with various alkenes using a nickel catalyst and triethoxysilane [(EtO)3SiH] as reducing agent was achieved. Under mild reaction conditions, both aliphatic and aromatic alkenes could react with nitroalkenes to obtain a series of olefins with different functional groups in satisfactory yields under an air atmosphere, which were previously difficult or impossible to access.